CAR T Cell Therapy for the Treatment of Medulloblastoma - Suk, Yujin (My University, 2024)
Medulloblastoma (MB) is the most common malignant pediatric brain tumour, comprised of four distinct molecular subgroups (WNT, SHH, Group 3, and Group 4). The standard of care (SoC) for MB patients involves maximal safe tumor resection followed by systemic chemoradiotherapy which can often lead to lifelong neurocognitive impairments in survivors. Group 3 and Group 4 make up the majority of MB patients but are the least defined in their oncogenic drivers and also have the highest propensity to present with metastasis at diagnosis. A subset of Group 3 MB tumors harbor focal amplifications of the MYC oncogene and are particularly prone to treatment resistance and leptomeningeal spread which remains incurable. Therefore, there is an urgent need for the development of therapeutic modalities that can spare the vulnerable, developing brain while having potent antitumour efficacy against recurrent MB. Chimeric Antigen Receptor (CAR) T cell therapies have shown tremendous success against hematological malignancies exhibiting its potential as an antitumor therapeutic modality given an effective target that is both (1) tumor-specific and (2) present at the cell surface to effectively direct its cytotoxic effects. Here, we explore the development and validation of both novel and established CAR T cell therapies for the treatment of Group 3 and Group 4 MB. We present extensive work covering novel target identification and validation, antibody and CAR T cell development, and preclinical combinatorial therapeutic modeling. These efforts highlight promising new therapeutic options for patients with aggressive and/or treatment-refractory forms of MB.
Keywords: Medulloblastoma; Brain Cancer; Immunotherapy; CAR T Cell Therapy; Cancer Biology; Nuclear Envelope Protein